Complementing the treatment of a major depressive disorder patient with Ruqyah Shar‘iyyah therapy: A Malaysian case study - Razali Z.A.; Rahman N.A.A.; Husin S. (Michigan Publishing, 2024)
This paper describes a female patient with major depressive disorder with psychotic features, who underwent mainstream psychiatric treatment complemented with ruqyah shar’iyyah (incantations based on Qur’an and prophetic traditions) healing in Malaysia. The patient faced the stigmatization of mental health within her family and had poor coping mechanisms, in addition to an incomplete understanding of what characterizes a religiously observant Muslim faith healer, in the early phases of her illness. The patient had periods of non-compliance with psychiatric care in between various ruqyah shar’iyyah, treatment periods, and faced a relapse that led to hospital admission. The patient’s outcome improved after she complemented her psychiatric treatment with ruqyah shar’iyyah, that complied with Islamic creed and law. The importance of the inter-related systems of medical and psycho-spiritual treatments needs to be emphasized as it is crucial to the psychological wellbeing of the patient. The case report illustrates that ruqyah shar’iyyah, a practice encouraged by the Prophet Muhammad is believed to be a therapeutic remedy for any disorder, and can be used as complementary spiritual-based treatment to mainstream psychiatry, bringing multiple benefits across various cultural groups of Muslims.